Christ's Depiction of Human Fragiilty In Byzantine Theology of Human Beings - Donald Steven Keryapi; Chainar Elly Ria; Murniati Barus (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study is to show the form of theology regarding human beings and how Christ takes on this human vulnerability, especially from the perspective of Byyantine theology. The methods used in this study are from the research literature. This is a kind of research model from a qualitative approach, and the research results are obtained from various literatures about the man of Christ from a Byzantine perspective. This study shows that man was originally the most glorious creature and was created in the image of God, Christ. Known in his two forms, Precariat and Precaritas, human vulnerability is the result of human sin. This state of human vulnerability was assumed by Christ through the Incarnation and the work of redemption that was accomplished so that man could reenter the communion of the Triune God through the theological process. Sacrament, especially the Eucharist or Holy Communion. The conclusion is that the frailty and instability of man's fragility is the result of sin He is one and accepted by Christ incarnate so that man may return to the communion of the Trinity God